Estrategias didácticas constructivistas para la generación de aprendizajes en Ciencias Naturales. Año lectivo 2021 – 2022 - Pacheco Cabrera, Fernando Israel (2022)
The application of constructivist and didactic strategies, promotes the participation and recreation of students while they build meaningful learning, that is why this research was carried out in order to enhance the achievement of learning in students, whose general objective is to promote the construction of significant learning in the subject of Natural Sciences, through the implementation of constructivist and didactic strategies, with the students of tenth year of EGBS of “Bernardo Valdivieso” High school. Academic year 2021 - 2022. To achieve the proposed objectives of this research, a qualitative methodology was used, which allowed to determine relevant characteristics of the educational environment, regarding the application of constructivist didactic strategies for the generation of learning in students. Likewise, from another classification criteria, the research belongs to a participatory action research type, resulting in a significant improvement in the teaching and learning process because both students and teacher worked with methods, techniques and resources that motivate the active participation of the learners and therefore the increase in their academic performance. The reached results denote a considerable improvement in terms of the achievement of significant learning in students, as a consequence of the application of pertinent didactic strategies and resources of a constructivist type, during the development and treatment of certain class topics. Keywords: Teaching-learning process, active participation, innovation, ICT.